The potential impact of intelligent power wheelchair use on social participation: perspectives of users, caregivers and clinicians. (May 2015) - Rushton, Paula W.; Kairy, Dahlia; Archambault, Philippe; Pituch, Evelina; Torkia, Caryne; El Fathi, Anas; Stone, Paula; Routhier, François; Forget, Robert; Pineau, Joelle; Gourdeau, Richard; Demers, Louise
Abstract Purpose: To explore power wheelchair users', caregivers' and clinicians' perspectives regarding the potential impact of intelligent power wheelchair use on social participation. Methods: Semi-structured interviews were conducted with power wheelchair users (n = 12), caregivers (n = 4) and clinicians (n = 12). An illustrative video was used to facilitate discussion. The transcribed interviews were analyzed using thematic analysis. Results: Three main themes were identified based on the experiences of the power wheelchair users, caregivers and clinicians: (1) increased social participation opportunities, (2) changing how social participation is experienced and (3) decreased risk of accidents during social participation. Conclusion: Findings from this study suggest that an intelligent power wheelchair would enhance social participation in a variety of important ways, thereby providing support for continued design and development of this assistive technology. Implications for Rehabilitation An intelligent power wheelchair has the potential to: Increase social participation opportunities by overcoming challenges associated with navigating through crowds and small spaces. Change how social participation is experienced through "normalizing" social interactions and decreasing the effort required to drive a power wheelchair. Decrease the risk of accidents during social participation by reducing the need for dangerous compensatory strategies and minimizing the impact of the physical environment.